2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids reduce interleukin‐1β concentration and result in neuroprotective effects in rat heatstroke

Abstract: In urethane‐anaesthetized rats, we assessed the protective effects of glucocorticoids against heatstroke‐induced arterial hypotension and ischaemic neuronal damage. Heatstroke was induced by exposing the animals to an ambient temperature of 42°C. The time at which both the mean arterial pressure (MAP) and local cerebral blood flow (CBF) in the striatum decreased from their peak levels was taken as the onset of heatstroke. Control rats were exposed to a temperature of 24°C. The values of MAP and CBF after heats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 28 publications
7
90
2
Order By: Relevance
“…Heatstroke rats displayed arterial hypotension, endotoxemia, cerebral ischemia (3,31), and reduced baroreceptor reflex response (32). Our recent results (10) further demonstrated that the heatstroke-induced ischemia, iNOS overexpression, and NO overproduction in rat brain can be suppressed by pretreatment with aminoguanidine (an iNOS inhibitor). It is likely that SMS may alleviate arterial hypotension as well as cerebral ischemia exhibited during the onset of heatstroke by reducing the iNOS-dependent NO overproduction.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Heatstroke rats displayed arterial hypotension, endotoxemia, cerebral ischemia (3,31), and reduced baroreceptor reflex response (32). Our recent results (10) further demonstrated that the heatstroke-induced ischemia, iNOS overexpression, and NO overproduction in rat brain can be suppressed by pretreatment with aminoguanidine (an iNOS inhibitor). It is likely that SMS may alleviate arterial hypotension as well as cerebral ischemia exhibited during the onset of heatstroke by reducing the iNOS-dependent NO overproduction.…”
Section: Discussionmentioning
confidence: 72%
“…For heatstroke induction, animals were exposed to a Ta of 43°C (with relative humidity of 60% in a temperature-controlled chamber). At a certain point in the heatstroke group, when MAP and local cerebral blood flow (CBF) in the striatum of rat brains began to decrease from their peak levels, this moment was considered as the onset of heatstroke (3,10). Immediately after the onset of heatstroke, heat stress was terminated and the animals were allowed to recover at room temperature (24°C).…”
Section: Experimental Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, increased levels of these cytokines are associated with heatstroke-induced arterial hypotension, cerebral ischemia, and neuronal damage (32,33; present results). Prior antagonism of ET A (present results) or IL-1b receptors (36,37) protects against heatstrokeinduced arterial hypotension, and cerebral ischemic damage and prolongs survival. As it is shown in the present results, prior antagonism of ET A receptors might exert its protective effects by attenuating the increased plasma level of TNF-a during heatstroke.…”
Section: Discussionmentioning
confidence: 95%
“…In the vehicle-treated heat stroke group, the animals were treated with an oral dose of DW (1 ml per rat daily and consecutively for 7 days) and exposed to heat stress (43°C). At a certain point, when MAP (mean arterial pressure) began to decrease from its peak level, this moment was arbitrarily defined as the onset of heat stroke (17,18). Immediately after the onset of heat stroke, heat stress was terminated and the animals were allowed to recover at room temperature (24°C).…”
Section: Animal Chow and Water Were Allowed Ad Libitummentioning
confidence: 99%